Rising mollusk bivalves from the ashes: Geologic, biostratigraphic and evolutionary implications from tuff data in the Permian Corumbataí Formation, Paraná Basin, Brazil - Christofoletti, B. [UNESP]; Warren, L. V. [UNESP]; Varejão, F. G.; Simões, M. G. [UNESP]; Gómez-Peral, L. E.; Lana, C.; Rodrigues, M. G. [UNESP]; Assine, M. L. [UNESP] (Elsevier, 2024)
During the Permian, the southwestern Gondwana margin experienced episodes of intense volcanism tied to the Choiyoi magmatism. Several ash-fall horizons related to this magmatic event are preserved within the Late Paleozoic lake-sea sedimentary record of the Paraná Basin. Furthermore, near the Permian-Triassic boundary, a meteor fell in the northern border of the basin, generating unshocked zircon grains preserved in a stratigraphic marker called the Porangaba Bed. In this study, a new U-Pb zircon age of 265.17 ± 3.2 Ma is presented for a volcanic tuff in the upper part of the Corumbataí Formation, near the stratigraphic interval of the Porangaba Bed. In addition, Lu-Hf isotopic compositions of the zircon grains, whole-rock geochemistry, and atmospheric circulation data indicate the affinity of the ash-fall horizon with the Frontal Cordillera source. The combination of these new and previous U-Pb ages allowed us to draw a more realistic scenario of the evolution of bivalve mollusk of the Corumbataí Formation and to improve the use of these macrofossils in the biostratigraphy of the Permian succession of the Paraná Basin. In this context, we established the limits of the Pinzonella neotropica-Jacquesia brasiliensis Association Biozone between 262.38 ± 5.7 Ma and 257.5 ± 2.2 Ma. Hence, in the north and central Paraná Basin the local resolution of this biozone is of ∼5 Ma. Moreover, the range of this biozone indicates that the endemic bivalves survived the end-Guadalupian (ca. 259 Ma) extinction event unscathed.
Keywords: Biostratigraphy; Choiyoi magmatism; Megalake; U-Pb age; Volcanic ash